Optimization Algorithm of Resources Limited and Time Least in Construction Project Management - Lan Li (2009 International Conference on Management and Service Science, 2009)
Resource optimization is an important content of project construction planning. As in some period resources required are more than resources available, construction planning has to be adjusted to satisfy resource restriction and not to delay the time or to get the least deferment. This paper presents the UTM algorithm for time parameters of construction schedule planning network diagram and resources optimization algorithm for "resources limited and time least", realizes rapid optimization computing with computer, and verifies validity of the algorithm by example.